The Leukocyte Digestion of Fibrinogen Degradation Products (FDP) - Gibiński, K; Lipiński, B; Trusz-Gluza, M (Thrombosis and Haemostasis, 1971)
While the native fibrinogen is not digested by the leucocyte proteases both the early and late FDP are digestible without any denaturating reagent. Thus, this reaction may occur in vivo indicating an unknown role of granulocytes in paracoagulation.